A comparison of two case studies illustrating the use of a collaborative information system to support competitive advantage. (1st January 1999) - Gunter, Karen; Butler, Paul
Companies are becoming increasingly interested in exploiting systems which support collaborative work, especially amongst knowledge workers who may be operating in geographically disparate locations, thus becoming part of a virtual team. The two case studies used in this paper consider the benefits of a collaborative information system (groupware combined with Web technology) to manage information that could lead to a competitive advantage. They are Intratech IS Bid and Southcom Competitive Intelligence. Both studies dealt with similar situations, they were centred around the collection and dissemination of information which would allow decisions to be taken that would affect the company's profitability. The results of these case studies serve to illustrate the approaches that must be taken to ensure the successful implementation of a collaborative information system.